How Corporate Brands Communicate their Higher Purpose on Social Media: Evidence from Top Global Brands on Twitter - C. Rudeloff; P. Michalski (Corporate Reputation Review, 2023)
Rising expectations in society for moral brand behavior have increased the relevance of brand purpose communication on social media. Nevertheless, there is a lack of fundamental research in this area. This study therefore examines brand purpose communication on Twitter, particularly with regard to the values addressed and the communication strategies implemented by corporate brands as well as the corresponding user engagement. A quantitative content analysis of 30 corporate Twitter accounts from 10 industries ( n 0.167em=0.167em6000) shows that brand purpose is communicated across all brands and industries. The values of solidarity and sustainability are in the foreground. In an industry comparison, the FMCG industry and the financial services industry communicate most frequently on brand purpose issues, whereas the media industry and the luxury goods industry do so only marginally. Corporate brands predominantly use information strategy to communicate their brand purpose, although the involvement strategy leads to more engagement. Overall, the analysis shows that the potential of brand purpose communication is not being exploited to the same extent in all industries.
Keywords: 330; Brand purpose; Social media; Twitter; Human values; Two-way communication; Symmetrical communication; Response; Involvement; Engagement; Stakeholder theory